ANALISIS KESALAHAN BERBAHASA INDONESIA DALAM PENULISAN LAPORAN PRAKTIKUM FISIKA DASAR PADA MAHASISWA SEMESTER I - Nurul Azizah; Cecillia Simanjuntak; Istika Dara Amalina; Nurul Zahra Sinaga; Zahrawani Dwiyarno (Didaktik : Jurnal Ilmiah PGSD STKIP Subang, 2026)
This study aims to identify language errors found in the Basic Physics practicum reports of first-semester students of PSPF 24 A class at Universitas Negeri Medan. The study employed a descriptive qualitative approach. Data were collected through documentation, observation, and note-taking techniques on students' practicum reports. The results revealed six language errors, which were classified into three categories: morphological errors, orthographic errors, and errors in writing physical unit symbols. Morphological errors were found in the use of non-standard words, orthographic errors were identified in the writing of reduplication, prepositions, and capitalization, while errors in physical unit symbols were related to the incorrect application of the International System of Units (SI). These findings indicate that students still encounter difficulties in applying Indonesian language rules and scientific writing conventions in practicum reports. Therefore, improving students' understanding of standard language usage and scientific writing conventions is necessary to enhance the quality of practicum reports.